Historical eruptions of Avacha volcano, Kamchatka. Attempt of modern interpretation and classification for long-term prediction of the types and parameters of future eruptions. Part 1 (1737-1909) - Melekestsev I.V.; Braitseva O.A.; Dvigalo V.N.; Bazanova L.I. (My University, 1994)
Some of the previous views on the style of the Avacha eruptions during 1737-1909 are revised on the basis of new data obtained by the authors. The types of eruptions, their geological and geomorphological effects, and the related volcanic hazards are reassessed. All eruptions were explosive events, except for the 1894-1895 extrusive-explosive eruption. The eruptions of 1737, 1779, and 1827 are classified as large, the others, as mild or medium-size events. -from Journal summary
Keywords: 38.37.25 Вулканология; Авачинский